Comparison of Efficacy of Halstead and Vazirani Akinosi Block Technique in Achieving Mandibular Anesthesia - Eruj Shuja, Sadia Daaniyal, Osama Mushtaq, Naseer Ahmed, Ammarah Afreen, Zarah Afreen, Eruj Shuja, Sadia Daaniyal, Osama Mushtaq, Naseer Ahmed, Ammarah Afreen, Zarah Afreen (Journal of Rawalpindi Medical College, 2022)
OBJECTIVE: To compare the efficacy of Halstead and Vasirani Akinosi block techniques in achieving mandibular anesthesia during exodontia among subjects reporting to Watim Teaching Hospital. STUDY DESIGN: Randomized controlled trial. PLACE AND DURATION OF STUDY: This study was conducted in the department of Maxillofacial Surgery, Watim Dental Hospital, Rawalpindi from July 2019 to January2020. MATERIALS AND METHODS: This is a randomized control trail of 60 patients. Duration of onset of anesthesia, pain during injection, incidence of aspiration, success and failure of Halstead and Vasirani Akinosi techniques and their mean doses were analyzed and compared by using SPSS version 17.Comparison of categorical variables was done by Chi-square test. Comparison of non-categorical variables was done by independent sample t-test. p value of less than 0.05 was considered significant. RESULTS: 28(93.3%) experienced moderate while 2(6.7%) experienced severe pain in Halstead group, while 30(100%) experienced mild pain in Vasirani Akinosi group. Halstead technique was successful in 22(73.3%) while unsuccessful in 8(26.7%) patients. Vasirani Akinosi technique was successful in 29(96.7%) and unsuccessful in 1(3.3%) patients. CONCLUSION: It may be concluded from analysis in the present study that Vasirani Akinosi technique was statistically superior in all parameters such as duration of onset, pain during injection, aspiration and success rate as compared to the conventional Halstead block technique. KEY WORDS: Extraction tooth, local anesthesia, Vasirani-Akinosi technique, nerve block.